2018
DOI: 10.1523/eneuro.0426-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Circadian and Brain State Modulation of Network Hyperexcitability in Alzheimer’s Disease

Abstract: Network hyperexcitability is a feature of Alzheimer’ disease (AD) as well as numerous transgenic mouse models of AD. While hyperexcitability in AD patients and AD animal models share certain features, the mechanistic overlap remains to be established. We aimed to identify features of network hyperexcitability in AD models that can be related to epileptiform activity signatures in AD patients. We studied network hyperexcitability in mice expressing amyloid precursor protein (APP) with mutations that cause famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 93 publications
6
29
0
Order By: Relevance
“…Therefore, the formation of amyloid plaques does not seem to be a trigger for inducing epileptiform activity. Given previous studies, the epileptiform discharges observed in the early stages in 5xFAD may be an effect of the overexpression of human amyloid precursor protein (APP) from the transgene [3,4]. Our results, however, strongly suggest that there is a link between the aggravation of epileptiform neuronal activity/convulsions and the observed changes in behavior after 28 weeks of age.…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, the formation of amyloid plaques does not seem to be a trigger for inducing epileptiform activity. Given previous studies, the epileptiform discharges observed in the early stages in 5xFAD may be an effect of the overexpression of human amyloid precursor protein (APP) from the transgene [3,4]. Our results, however, strongly suggest that there is a link between the aggravation of epileptiform neuronal activity/convulsions and the observed changes in behavior after 28 weeks of age.…”
Section: Discussionsupporting
confidence: 55%
“…4b ). A previous comparison of J20 mice with App NL-F knock-in mice detected epileptiform activity in the former but not the latter model [ 101 ], but this difference is difficult to interpret because of the much lower Aβ levels in the App NL-F knock-in mice (Additional File 1 : Figure S1b).
Fig.
…”
Section: Resultsmentioning
confidence: 86%
“…Mounting evidence from mouse model studies suggest that, in the amyloid-depositing brain, functional impairments of local neuronal circuits lead to disruption in the E/I balance, which then result in large-scale networks defects (Busche et al, 2008; Busche and Konnerth, 2016; Palop and Mucke, 2016). Loss of inhibitory interneurons results in impaired oscillatory rhythm (Ramos et al, 2006; Baglietto-Vargas et al, 2010; Verret et al, 2012) leading to epileptiform activity (Vossel et al, 2016) and network hyperexcitability (Brown et al, 2018) in a subset of AD patients. Some studies have reported reduction of inhibitory pre-synaptic VGAT and GAT1 peri-somatic terminals on pyramidal neurons close to plaques, both in AD post mortem cases and aged APP/PS1 mice (Garcia-Marin et al, 2009).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%